2021
DOI: 10.1242/dmm.045963
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of murine copper homeostasis by members of the COMMD protein family

Abstract: Copper is an essential transition metal for all eukaryotes. In mammals, intestinal copper absorption is mediated by the ATP7A copper transporter, whereas copper excretion occurs predominatly through the biliary route and is mediated by the paralog ATP7B. Both transporters have been shown to be actively recycled between the endosomal network and the plasma membrane by a molecular machinery known as the COMMD/CCDC22/CCDC93 or CCC complex. In fact, mutations in COMMD1 can lead to impaired biliary copper excretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…COMMD1, by far, is the only identified membrane trafficking regulator with Cu-binding capability that directly mediates cellular Cu homeostasis [ 106 , 179 , 180 ]. Recent studies in tissue-specific knockout mice suggested that, within the COMMD family, Commd6 and Commd9 might also play a similar role as Commd1, since mice with liver-specific deficiency on Commd1, Commd6 or Commd9 shared the same Cu accumulation phenotype in the liver [ 235 ]. Further, COMMD1 has been reported to regulate the trafficking of ATP7A and ATP7B, whose functions and distributions are similar but not identical [ 86 ].…”
Section: Conclusion Remarks and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…COMMD1, by far, is the only identified membrane trafficking regulator with Cu-binding capability that directly mediates cellular Cu homeostasis [ 106 , 179 , 180 ]. Recent studies in tissue-specific knockout mice suggested that, within the COMMD family, Commd6 and Commd9 might also play a similar role as Commd1, since mice with liver-specific deficiency on Commd1, Commd6 or Commd9 shared the same Cu accumulation phenotype in the liver [ 235 ]. Further, COMMD1 has been reported to regulate the trafficking of ATP7A and ATP7B, whose functions and distributions are similar but not identical [ 86 ].…”
Section: Conclusion Remarks and Perspectivesmentioning
confidence: 99%
“…Current molecular understanding of Cu transporters trafficking is mainly originated from non-neuronal cells. This could be a concern since Cu homeostasis and the trafficking of Atp7a show drastic differences between mice intestine and liver cells [ 235 ]. This observation suggests potential differences in the trafficking of neurons and non-neuronal cells that were primarily neglected in the past.…”
Section: Conclusion Remarks and Perspectivesmentioning
confidence: 99%
“…In contrast, intestinal deletion of COMMD1 (and COMMD9) did not show altered Cu levels in enterocytes. Moreover, these animals did not show reduced serum ceruloplasmin levels when fed ammonia tetrathiomolybdate, a specific Cu chelator that induces Cu deficiency in animals, demonstrating organ-specificity of COMMD's functions [50].…”
Section: Cu-atpases In Pt Drugs Effluxmentioning
confidence: 89%
“…COMMD1 is also required for ATP7B trafficking [52]. Hepatic deletions of COMMD1 results in accumulation of Cu and development of Cu toxicosis in the livers [50,53]. In contrast, intestinal deletion of COMMD1 (and COMMD9) did not show altered Cu levels in enterocytes.…”
Section: Cu-atpases In Pt Drugs Effluxmentioning
confidence: 98%
See 1 more Smart Citation